Healing Without Borders: Addressing the Health Needs of Refugees - CheMan, Zuraidah; Mohamad Habibullah, Siti Noraida; Yeo, Jason (International Journal of Human and Health Sciences (IJHHS), 2025)
The global refugee crisis presents complex challenges for health providers and displaced populations. This symposium aims to address key areas impacting refugee health, focusing on the multifaceted barriers faced by both health professionals and refugees. Panellists from non-governmental organizations (NGOs), the UNHCR, and healthcare institutions will explore the pressing issues of delivering holistic health services, including sexual and reproductive healthcare, in refugee communities. Discussions will also highlight the challenges related to cultural and language barriers, limited healthcare infrastructure, and mental health needs. In addition, the symposium will cover the latest updates on policies and global efforts to improve healthcare access and outcomes for refugees. By integrating perspectives from various stakeholders, the session will provide a comprehensive understanding of the current landscape and offer practical solutions to enhance the delivery of essential health services to vulnerable populations. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S13